Integrasi Pendidikan Islam (Nilai-Nilai Islami dalam Pembelajaran) - Afiful Ikhwan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
The integration of education and Islamic values in teaching and learning must be conducted by not making dichotomy of knowledge. The integration of Islamic values is conducted in term: first, the wholeness of integration in which Islamic value is integrated in all subject matters. Second, the variety of model, method, and approach in integrating Islamic values which is applied by the teachers in the teaching and learning process. Third, the integration of Islamic values at school and at students’ home in which there is a coordination between school and parents to implement the teaching of Islamic values.